Investigation of the B-24 H Liberator “Lady Luck” heavy bomber in the waters off the island of Biševo (In situ, 2025)
It is known that on November 17, 1944, the Allied forces sent 630 fighter planes on a bombing mission to the industrial zone of Vienna. The B-24H bomber #42-52774, nicknamed “Lady Luck”, under the command of pilot Henry Mills, also participated in the mission. Although the mission's objective was successfully achieved, the bomber's engines were damaged by anti-aircraft fire, which caused the plane to crash while attempting to land at Vis airport. The underwater archaeological site with the remains of the wreck is located west of the island of Biševo and includes a total of three positions (L 1-3), at an average depth of 90 meters. The search was initiated by the Missing Persons Agency (DPAA), under the leadership of the RPM Nautical Foundation, in cooperation with partners and external contractors, with the aim of finding the remains of the deceased crew members, and then repatriating them to the United States of America. In 2024, the third research campaign was carried out in which, after the documentation of the existing condition using remote methods and photogrammetry, excavation continued in targeted trial trenches at position 1 (L 1), where most of the bomber's parts are located (fuselage, tail, wings). The article describes the course of the research campaign, work methodology and interventions at the underwater site.
Keywords: heavy bomber; Lady Luck; island of Biševo